ER-associated ubiquitin ligase HRD1 programs liver metabolism by targeting multiple metabolic enzymes - Juncheng Wei (Nature Portfolio, 2018)
HRD1 is an E3 ligase known to play a role in targeting degradation of misfolded proteins in the ER. Here the authors show that HRD1 interacts with metabolic enzymes and its liver specific deficiency results in lower body weight, blood glucose and plasma lipids during high fat diet in mice.